Mast cell protecting effects of shilajit and its constituents - Ghosal S.; Lal J.; Singh S.K.; Dasgupta G.; Bhaduri J.; Mukhopadhyay M.; Bhattacharya S.K. (My University, 2025)
The effects of shilajit and the combined effects of its main constituents, fulvic acids (FAs), 4′‐methoxy‐6‐carbomethoxybiphenyl (MCB) and 3,8‐dihydroxy‐dibenzo‐α‐pyrone (DDP), were studied in relation to the degranulation and disruption of mast cells against noxious stimuli. Shilajit and different combinations of FAs, MCB and DDP provided statistically significant protection to antigen‐induced degranulation of sensitized mast cells, markedly inhibited the antigen‐induced spasm of sensitized guinea‐pig ileum, and prevented mast cell disruption induced by compound 48/80. The findings are appraised in view of the clinical use of shilajit in the treatment of allergic disorders in Ayurvedic medicine. Copyright © 1989 John Wiley & Sons, Ltd.